106k views
4 votes
Write the trigonometric expression in terms of sine and cosine, and then simplify. sin(u) cot(u) cos(u)

User Joel Hinz
by
5.7k points

2 Answers

3 votes

Final answer:

To rewrite the trigonometric expression in terms of sine and cosine, we can use trigonometric identities to express the expression in a more simplified form.

Step-by-step explanation:

To write the trigonometric expression in terms of sine and cosine and simplify, we can use the following trigonometric identities:

  1. sin(u) = sin(u)
  2. cot(u) = 1/tan(u)
  3. cos(u) = √(1-sin²(u))

Using these identities, we can rewrite the expression as:

sin(u) * (1/tan(u)) * √(1-sin²(u))

Then, we can simplify further if needed.

User Mo Moosa
by
4.9k points
3 votes

Answer:


sin(u) cot(u) cos(u) = cos^(2)(u)

Step-by-step explanation:


sin(u) cot(u) cos(u)

First, let us simplify cot(u) as follows:

cot (u) =
(1)/(tan(u))

also,
tan (u) = (sin (u))/(cos(u))


(1)/(tan(u)) = (1)/((sin(u))/(cos(u)) ) = (cos(u))/(sin(u))

Hence the original expression becomes:


sin(u).(cos(u))/(sin(u)) .cos(u)

Next, sin(u) will cancel each other out, leaving the expression below:


cos(u) . cos(u) = cos^(2) (u)

hence:


sin(u) cot(u) cos(u) = cos^(2)(u)

I also found a similar expression with a plus (+) sign after the "sin(u)" online, and if this was your question, the solution will be as follows:

sin(u)+ cot(u) cos(u)


sin(u) + (cos(u))/(sin(u)) . cos (u)


= sin(u) + (cos^(2) (u))/(sin(u))


sin(u).(sin(u))/(sin(u)) + (cos^(2)(u) )/(sin(u)) \\ (note that
(sin(u))/(sin(u)) = 1, hence multiplying it with sin(u) does not change anything in the expression.)


(sin^(2) (u))/(sin(u)) + (cos^(2)(u) )/(sin(u)) = (sin^(2)(u) + cos^(2)(u) )/(sin(u))

Now the relationship sin²(u) + cos²(u) = 1

Therefore:


(sin^(2)(u) + cos^(2)(u) )/(sin(u)) = (1)/(sin(u))

Hence,
sin(u)+ cot(u) cos(u) = (1)/(sin(u))

User Frank N Stein
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.